Konsep Kecemasan dalam Perspektif Al-Quran dan Psikologi Modern - Cita Aprilda Kirana; Ahmad Nurrohim (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The most effective means of mitigating the harmful effects of mental health issues are urgently needed. Among the many mental health issues that people face, anxiety disorders rank high. This disease affects people all throughout the world, especially in Indonesia. In this post, we will take a look at the concept of anxiety in the Quran and compare it to how modern psychology understands it. With reference to the Quran, anxiety is understood as a test that can be overcome through faith and obedience to Allah. Meanwhile, modern psychology views anxiety as a natural response to stress and threat, which can be managed through cognitive and behavioral techniques. Through this comparative approach, a common ground can be found between religious views and modern science in understanding and managing anxiety.